Free Kick achievement Based on Distance and Ball Position - Hendri Hendri; Yohanes Touvan Juni Samodra; Rubiyatno Rubiyatno; Eka Supriatna; Putra Sastaman B (Universitas Majalengka, 2023)
Mastery of kicking for soccer players is very important. Shooting the ball at a shooting range is very important because it cannot be ensured that the shooting distance is always at the same distance; additional accuracy at several distances is needed for every player. The purpose of this study is to describe the ability to kick a ball as measured by shot accuracy at a distance of 17 metres, 23 metres, and 38 metres. The research sample consisted of 30 soccer players from the two PSPP Pampang and Samustida FC football clubs. Based on the tests conducted and after analysis, it turned out that the accuracy of kicks by football players at these two clubs still tended to be low and very lacking. Further evidence from the different tests that were carried out also showed that there was no difference in the ability to kick the ball at several specified distances.